A 2.09 Mb fragment translocation on chromosome 6 causes abnormalities during meiosis and leads to less seed watermelon. (1st December 2021) - Tian, Shujuan; Ge, Jie; Ai, Gongli; Jiang, Jiao; Liu, Qiyan; Chen, Xiner; Liu, Man; Yang, Jianqiang; Zhang, Xian; Yuan, Li
Abstract: Seedlessness is a valuable agronomic trait in watermelon ( Citrullus lanatus ) breeding. Conventional less seed watermelons are mainly triploid, which has many disadvantages due to unbalanced genome content. Less seed watermelon can be achieved at the diploid level when certain reproductive genes are mutated or by chromosome translocation, which leads to defects during meiosis. However, the formation mechanism of diploid less seed watermelons remains largely unknown. Here, we identified a spontaneous mutant line, watermelon line "148", which can set seeds normally when self-pollinated. A total of 148 × JM F1 hybrid plants exhibited seed number reductions to 50.3% and 47.3% of those of the two parental lines, respectively, which are considered to be less seed. Examination of pollen viability and hybridization experiments revealed that F1 hybrids produce semisterile pollen and ovules. Further cytological observations indicated that semisterility was a result of a reciprocal translocation of chromosomes, which exhibited one quadrivalent ring of four chromosomes at prometaphase I during meiosis. RT-qPCR analysis indirectly confirmed that the semisterile phenotype is caused by chromosome translocation rather than disruption of specific meiotic gene expression. F2 population genetic analysis indicated that the "148" watermelon line is a homozygous translocation and that the less seed phenotype of the F1 hybrid is prompted by one chromosome fragment translocation. The translocated fragment was further fine mapped to a 2.09 Mb region on chromosome 6 by whole-genome resequencing and genetic map cloning procedures. Our work revealed that a 2.09 Mb chromosome fragment translocation on chromosome 6, causing meiotic defects at metaphase I during meiosis, leads to diploid less seed watermelon. Our findings provide a new promising method for less seed watermelon breeding at the diploid level, as well as a fragment size reference for breeding less seed watermelon through artificially induced chromosome translocation.